Assessment of the anti-metastatic properties of sanguiin H-6 in HUVECs and MDA-MB-231 human breast cancer cells. Issue 14 (15th July 2016) - Park, Eun-Hwa; Park, Jun Yeon; Yoo, Hwa-Seung; Yoo, Jeong-Eun; Lee, Hye Lim
Graphical abstract: Abstract: The anti-metastatic properties of sanguiin H-6 were examined in human umbilical vein vascular endothelial cells (HUVECs) and MDA-MB-231 human breast cancer cells. In HUVECs, sanguiin H-6 inhibited the density of migrated cells compared to that observed after treatment with the vehicle. In addition, sanguiin H-6 at a concentration of 6.25 μM significantly blocked tube formation. Treatment with up to 25 μM sanguiin H-6 had no effect on MDA-MB-231 cells, whereas treatment with 200 μM sanguiin H-6 decreased cell viability. Sanguiin H-6 significantly decreased the expression levels of vascular endothelial growth factor (VEGF), phosphorylated Akt, and extracellular signal-regulated kinase 1/2 (ERK1/2) in MDA-MB-231 cells. These findings suggest that sanguiin H-6 is potentially useful as an anti-metastatic agent.